The Impact of Diversification on Performance of Lloyd’s Syndicates: a Mixed Methods Analysis - Sylvester, Sam (2012)
The goal of this project is to understand the effect of diversification on the performance of Lloyd’s syndicates and the reasons for that effect. The Literature Review highlights the difficulties in answering this question. With conflicting theories and empirical studies, there are gaps and ambiguities in the literature, which make it hard to assess whether diversification should have a positive impact on performance. The relevance of different costs and benefits, the impact on investor value, and the importance of core competences are all open to question based upon the literature. The research undertaken is designed to fill these gaps and clarify the ambiguities. A mixed method approach is taken, generating hypotheses from qualitative research and testing these hypotheses with the quantitative research. In discussing the results from the research and how they relate to the literature, several implications for syndicate stakeholders are identified, leading to several recommendations. These recommendations support the conclusion, that diversification can improve the performance of Lloyd’s syndicates, but it must be done in the right way, with emphasis on profit, management skill and underwriting skill.